The only beginner freeze-drying book you'll ever need : learn the simple process to create food storage for your survival pantry and discover easy recipes your family will love (Micro-Homesteading Education, 2023)
"With this book, you can follow a proven systematic approach to freeze-drying with all the information and worksheets needed to guide you through each step of the process, from selection and preparation to packaging and storage. You can skip the research and start benefiting from freeze-dried foods right from the start." -- back cover.